MODEL OF DEVELOPMENT OF TEACHING MATERIALS FOR ARABIC LANGUAGE SKILLS AT AL MAAHIRA IIBS MALANG "AL-HIWARAT AL-YAUMIYAH" - Ummu Salamah; Muhammad Jailani; Slamet Daroini (Kitaba, 2024)
IIBS Al Maahira Malang. This institution is a boarding school based on Islam and international standards. So, the lessons in it must more or less use the language of AISNG. This includes learning Arabic. Here, the researcher will specialize more on learning Arabic in Islamic boarding schools. Currently, Al-Maahira has an Arabic textbook called "Al-Hiwarat Al-Yaumiyah." In it there are several maharatul kalam combinations from a technical point of view, for example, it even contains several friends related to daily life and of course many collections of mufrodat that are relevant to the themes in it. This research aims to determine the feasibility of Arabic textbooks used at IIBS Al-Maahira. Knowing the presentation of Arabic textbooks at IIBS Al-Maahira. Knowing the background of the development of teaching materials at IIBS Al-Maahira. This study uses a qualitative method with a field observation process carried out by the researcher. The results were obtained: First, the development of the maharatul kalam textbook is the initial solution to the problem of students' language from the beginning of the institution's pioneering. Second, this textbook is compiled by involving material experts, learning media experts, linguists, and of course the language section at Al-Maahira IIBS. Third, this textbook is systematically arranged with the division of themes, the existence of mufrodat related to the theme, conversations related to the theme. And special guidance for teachers in delivering material.